Anti-neuroinflammatory effect of hydroxytyrosol: a potential strategy for anti-depressant development - Li, Shuaiguang; Shao, Huarong; Sun, Ting; Guo, Xinyan; Zhang, Xiaoyuan; Zeng, Qingkai; Fang, Shaoying; Liu, Xiaoyu; Wang, Fan; Liu, Fei; Ling, Peixue (Frontiers in Pharmacology, 2024)
Depression is a complex psychiatric disorder with substantial societal impact. Current antidepressants, though moderately effective, have adverse effects and an incomplete understanding of depression's pathophysiology impedes the development of more effective treatments. In this challenging context, the role of neuroinflammation, a known but poorly understood associate of depression, has gained increasing attention. This study investigates hydroxytyrosol (HT), an olivederived phenolic antioxidant, for its antidepressant and anti-neuroinflammatory properties based on mitochondrial protection. In vitro studies on neuronal injury models, supplemented with highresolution imaging of mitochondrial substructures, demonstrate HT's capability to protect mitochondrial ultrastructure from inflammatory damage, thus exerting neuroprotective effects. In animal models, HT reduced depressive-like behaviors in mice and rats exposed to chronic restraint stress (CRS) and chronic unpredictable mild stress (CUMS), respectively. HT's influence in the CRS model included alleviating hippocampal neuronal damage and modulating cytokine production, mitochondrial dysfunction, and brain-derived neurotrophic factor (BDNF) signaling. Targeted metabolomics in CUMS rats revealed HT's effect on neurotransmitter levels and tryptophankynurenine metabolism. RNA-Seq data underscored HT's antidepressant mechanism through the BDNF/TrkB signaling pathways, key in nerve fiber functions, myelin formation, microglial differentiation, and neural regeneration. These results highlight HT's potential as an anti-